DEBRIDEMENT WITH FASCIOTOMY ON DIABETIC FOOT REDUCES TUMOR NECROSIS FACTOR ALPHA AND INCREASES VASCULAR ENDOTHELIAL GROWTH FACTOR PLASMA WITH CLINICAL IMPROVEMENT - Yasa, K. P.; Siki-Kawiyana, K.; Budhiartha, A.A. G. (BALI MEDICAL JOURNAL, 2014)
Background: Clinical and animal studies find out any increase of TNF-? and decrease of VEGF level  in tissues of diabetic foot ulcers. Levels and abnormal activity of VEGF related to hypoxia and  increase of TNF-? in diabetic tissue lead to impaired healing of ulcers. This study aims to determine  debridement with fasciotomy simultaneously reduce TNF-? and increases VEGF plasma level and  clinical improvement of diabetic foot ulcers. Methods: A clinical study by a randomized pretest - posttest control group design was carried out. Patients were divided into two groups of debridement without fasciotomy as a control group and group of debridement with fasciotomy as the treatment group. Sixty patients of diabetic foot ulcer Wagner II, III, and IV classification met inclusion and exclusion criteria, 28 patients were selected as control group and 32 as treatment group. Clinical improvement of ulcers was observed every week for 4 weeks using the instrument of Leg Ulcer Measurement Tool (LUMT) score.  Result: Plasma TNF-? pretest was 422.30±17.05 (pg/ml) on control group and 424.47±12.02 (pg/ml) on treatment group. Plasma TNF-? posttest was 390.91±12.85 (pg/ml) on control group and 290.26±16.42 (pg/ml) on treatment group ( p <0.05), with ? TNF-? (pg/ml) was 31,40±17,98 on control group and 134.21±14.50 on treatment group ( p <0.05). Plasma VEGF level (pg/ml) pretest was 282.50±11.58 on control group and 286.74±10.19 on treatment group. Plasma VEGF level (pg/ml) posttest was 289.19±21.91 on control group, 338.70±20.11 on treatment group ( p <0.05), with ? VEGF (pg/ml) was 15.23±10.73 on control group and 51.96±13.54 on treatment group ( p <0.05). There was significant clinical improvement of ulcer on treatment group on 2nd , 3rd, and 4th week of treatment ( p <0.05) There was average increase pressure (13-21 mmHg) on all foot compartments of the two groups  Conclusion: debridement with fasciotomy simultaneously decreases TNF-? and increases VEGF plasma level accompanied clinical improvement of diabetic foot ulcer. Increase of foot compartment pressure may support phenomenon of microvascular permeability on diabetic patients, therefore fasciotomy on diabetic foot to become rational as adjunct of treatment.
Keywords: diabetic foot, debridement, fasciotomy, TNF-?, VEGF, clinical improvement